Mathematical Analysis of Fertility in Nepal Using Arriaga's Approach - Kumar, Nand Kishor; Yadav, Dipendra Prasad (Darul Yasin Al Sys, 2024)
This article has judged how well the P/F changing ratio technique and Arriaga's approach forecast fertility levels in Nepal. The study's goal was accomplished and the logistic curve function was legalized by estimating national fertility rates. Using information from the 2011 till 2021 censuses together with Arriaga's methodology, the following factual investigates the calculation of fertility rates in Nepal. By using cutting edge indirect fertility estimation techniques on a national level, this study seeks to evaluate the fertility change in Nepal. Utilizing information from the 2011 and 2021 Censuses, fertility estimates were produced with an emphasis on last-year births. The findings show that Nepal's fertility rates have recently dropped.